2017
DOI: 10.7196/samj.2017.v107i3.12035
|View full text |Cite
|
Sign up to set email alerts
|

A framework for preventing healthcare-associated infection in neonates and children in South Africa

Abstract: Healthcare-associated infection (HAI) is a frequent and serious complication affecting 4 -8% of hospitalised children and neonates in high-income countries. The burden of HAI in South African (SA) paediatric and neonatal wards is substantial but underappreciated, owing to a lack of HAI surveillance and reporting. Maternal and child health and infection prevention are priority areas for healthcare quality improvement in the National Core Standards programme. Despite increasing recognition in SA, infection preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 21 publications
1
30
0
1
Order By: Relevance
“…The fourth major barrier identi ed was a chronic lack of equipment, medication, and other resources in the facilities, also documented in previous studies in South Africa (2,35,39) and within the Agincourt HDSS study area. (40,41) A 2018 study intervention to improve hypertension care in PHCs in the Agincourt HDSS was unsuccessful, in part due to unreliable blood pressure machines and cuffs, intermittent drug shortages, and lack of space.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The fourth major barrier identi ed was a chronic lack of equipment, medication, and other resources in the facilities, also documented in previous studies in South Africa (2,35,39) and within the Agincourt HDSS study area. (40,41) A 2018 study intervention to improve hypertension care in PHCs in the Agincourt HDSS was unsuccessful, in part due to unreliable blood pressure machines and cuffs, intermittent drug shortages, and lack of space.…”
Section: Discussionmentioning
confidence: 64%
“…Healthcare associated infections have been noted in past research due to aging infrastructure and inadequate environmental cleaning. (35) Other research has found poor hygiene and infection control in South African healthcare facilities. (2,19) Structural issues noted by providers such as leaking roofs, collapsed ceilings, insect and bat infestations, all require immediate attention and maintenance to ensure safe environments for providers and patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Healthcare-associated infections (HAI), also known as nosocomial infections, are acquired by patients during the process of care in a hospital or other healthcare facility [1,2]. Such infections are major contributors to morbidity and mortality and point to insufficient hygiene practices within the healthcare facility [3,4]. The propagation of HAI either occurs through parenteral or airborne transmission, in addition to hand contamination [3].…”
Section: Introductionmentioning
confidence: 99%
“…12 Esa facilidad de adquirir una infección asociada a la atención de la salud se explica porque los recién nacidos tienen una respuesta inmune innata subdesarrollada a la infección por la baja producción de citoquinas, una pobre función de neutrófilos y células dendríticas en comparación con las de los adultos, lo cual incrementa el riesgo de desarrollar infecciones bacterianas, fúngicas y virales. No obstante, cabe aclarar que los recién nacidos pretérminos tienen mayor susceptibilidad a la sepsis y a un mayor riesgo de complicaciones a largo plazo y mortalidad que los recién nacidos de término 13 ; por lo tanto, la prevención de las infecciones intrahospitalarias es una prioridad de salud pública que se encuentra en constante revisión para establecer los programas de vigilancia y prevención de las IAAS que mejoren la calidad de la atención sanitaria 14 , por lo que la formación y participación de un sistema de vigilancia local es muy importante para que -por medio de la interpretación de los datos obtenidos-se utilicen en la gestión interna de la calidad de la atención sanitaria para la reducción de las IAAS, ya que el sistema permitiría identificar factores de riesgo no reconocidos que deben tomarse en cuenta en el proceso de evaluación, lo cual tendría como efecto directo la reducción sustancial de las tasas de IAAS 15 .…”
Section: Introductionunclassified